Estudios sobre la fertilidad y compatibilidad sexual del hongo Pyricularia grisea (Sacc) y sus implicaciones en el desarrollo de resistencia durable en variedades de arroz para Colombia - Prado Patiño, Gustavo A.; Correa Victoria, Fernando J. (2000)
Rice blast caused by the fungus Pyricularia grisea (Sacc) is the major constraint of the crop. Development of resistant varieties has been the preferred means to control blast, however, resistance breakdown occurs shortly after varietal release, due to the appearance of new races of the pathogen. It has not been possible to determine the possible mechanisms used by the fungus for originating pathogenic variation. The objective of this work was to study under laboratory conditions if Colombian isolates of P. grisea collected on rice and weeds might use sexual reproduction to generate pathogenic variability, and to determine the breeding implications of the results for the development of resistance to blast followed at CIAT. During this research 99 blast isolates collected on rice, and 56 from weeds were used. The isolates were classified into four groups according to their genetic characteristics, mating type, and/or origin and their importance for breeding strategies. Each isolate within a group was paired with the others in all possible combinations. Crosses were made on artificial medium giving all optimal conditions to favor the development of the sexual stage, according to the literature. Formation of perithecia was not observed for any combination in any of the four groups. The results suggest that sexual reproduction was not possible in the population of the blast pathogen studied, indicating that this mechanism is not playing an important role in generating pathogenic variability in the fungus in Colombia. This observation supports the breeding strategies implemented at CIAT for developing resistant varieties. These strategies are based on the accumulation of resistance genes specific to different genetic families of the fungus. The lack of the sexual stage implies that accumulation of virulence genes specific to certain resistance genes is of low probability. It is recommended to study the effect of other possible mechanisms of reproduction that may play a role in generating pathogenic variability such as the parasexual cycle and mutations.